PENDIDIKAN KARAKTER DI LINGKUNGAN KELUARGA SELAMA PEMBELAJARAN JARAK JAUH PADA MASA PANDEMI COVID 19 - Enur Aini Indriyani; Ansori Ansori; Nunu Mahmud Firdaus (IKIP Siliwangi, 2022)
This research is motivated by how the growth of character education in the family environment during distance learning from home. One of the important concepts of the role of parents in the process of character education of children during the Covid-19 pandemic is to be a good facilitator for children in learning the three main material points of character education, namely issues of belief or religious education, problems of social interaction or social education, and the problem of habituation of good activities or moral education on character values such as (religious, disciplined, creative, independent, and responsible). The method used in this research is a qualitative method with a case study approach. The subjects of this study were teachers, parents of school students in Nunuk Village, Cililin Village, Cililin District, West Bandung Regency as many as 5 people’s. The results of this study indicate that the approach in the family environment in instilling character education in students during distance learning during the Covid 19 pandemic. How to instill character education in students during distance learning during the Covid 19 pandemic in the family environment through the formation of character values such as (religious, disciplined, creative, independent, and responsible). Obstacles encountered by families in instilling character education in students during distance learning during the Covid 19 pandemic. During the current pandemic, children spend more time in an environment other than the school environment, such as the family environment and social community with their playmates, although in limited numbers.